Combination of Fusiform Capsulectomy of the Posterior Capsule and Percutaneous Flexion Tendon Release in the Treatment of Fused Knee with Severe Flexion Contracture During Total Knee Arthroplasty—A Report of Six Cases - Chen, Qun-Qun; He, Min-Cong; Cao, Zheng; Kong, Xiang-Peng; Wang, Hai-Bin; Chai, Wei (Frontiers in Surgery, 2022)
Abstract Purpose: This clinical research aimed to assess the safety and efficacy of combination of fusiform capsulectomy of posterior capsule and percutaneous flexion tendon release in the treatment of fused knee with severe flexion contracture during total knee arthroplasty (TKA). Methods A retrospective analysis was performed in 3 patients (6 knees) who had preoperative severe bony fused flexion contracture (>80 degrees) prior to TKA and received combination of fusiform capsulectomy of posterior capsule and percutaneous flexion tendon release during TKA between January 2016 and December 2019. Range of motion (ROM), knee functional score, post-operative complications, and radiographic results were evaluated. Result: Three patients (6 knees) were enrolled in this study. The mean duration of follow-up was 42.83 ± 15.77 months. The post-operative knee ROM was 100.0 (76.0, 102.75) (p<0.01). KSS clinical score increased from pre-operative 30.0 (25.0, 36.0) to post-operative 64.0 (65.0, 78.0) (p<0.01), and KSS function score increased from pre-operative 0.0 (0.0, 30.0) to post-operative 55.0 (40.0, 55.0) (p<0.01). No implant loosening, infection, neurovascular complications, or revision were recorded in the cohort until the last follow-up. Conclusions: The technique of combination of fusiform capsulectomy of posterior capsule and percutaneous flexion tendon release is one effective and safe method during primary TKA for fused knee with severe flexion contracture.